Graphitic carbon nitride (g-C3N4)-based photocatalysts for water disinfection and microbial control: A review - Zhang, Chi; Li, Yi; Shuai, Danmeng; Shen, Yun; Xiong, Wei; Wang, Linqiong (Chemosphere (Oxford), 2019)
Microbial contamination in drinking water is of great concern around the world because of high pathogenic risks to humans. Semiconductor photocatalysis has aroused an increasing interest as a promising environmental remediation technology for water disinfection and microbial control. Among various photocatalysts, graphitic carbon nitride (g-C3N4), as a fascinating two-dimensional conjugated polymer consisting of low-cost, earth-abundant elements, has drawn broad attention as a robust, metal-free, and visible-light-active material in the fields of both environmental remediation and solar energy conversion. Photocatalytic applications of g-C3N4-based nanomaterials for water splitting, hydrogen production, carbon dioxide reduction, and pollutant degradation have been extensively investigated and systematically reviewed. In contrast, their antimicrobial properties have been explored more recently due to the complex structure and unique metabolism of living microorganisms compared with chemicals. The corresponding rapidly increasing research efforts in the last five years have inspired us to conduct the review. This review is the first to comprehensively summarize the progress in design and antimicrobial performance of g-C3N4-based photocatalysts for water disinfection and microbial control, involving not only bacteria but also viruses and microalgae. Moreover, the underlying inactivation mechanisms of photocatalysts for microorganisms are evaluated to provide further understanding of g-C3N4-based advanced disinfection processes. In addition, some exciting future opportunities and challenges at the forefront of this research platform are pointed out. It is expected that this review can pave a new avenue for the development of a facile, cost-effective, environmental-friendly, and sustainable disinfection alternative. •An overview of design and performance of g-C3N4-based antimicrobials is presented.•Collaboration of photocatalysts with microorganisms is also introduced.•Microbial inactivation mechanisms in two different perspectives are discussed.•Future perspectives for g-C3N4-based antimicrobials are pointed out.